Транспорт наносов внутренними волнами - Слепышев, A.A.; Носова, А.В. (Видавничий дім "Академперіодика" НАН України, 2007)
In the Boussinesq approximation, the mean flows induced by a wave through nonlinearities in the presence of eddy viscosity are determined for internal waves. The boundary layer solutions, decrement of fading of a wave, and tangential stress at the bottom are determined. The bottom concentration of wave-suspended sediments is obtained when the bottom stress exceeds a critical value. The vertical distribution of the concentration of sediments is determined in the diffusion approximation.